2018
DOI: 10.1371/journal.pone.0205042
|View full text |Cite
|
Sign up to set email alerts
|

RAIDD mutations underlie the pathogenesis of thin lissencephaly (TLIS)

Abstract: Abnormal regulation of caspase-2-mediated neuronal cell death causes neurodegenerative diseases and defective brain development. PIDDosome is caspase-2 activating complex composed of PIDD, RAIDD, and caspase-2. Recent whole-exome sequencing study showed that the RAIDD mutations in the death domain (DD), including G128R, F164C, R170C, and R170H mutations, cause thin lissencephaly (TLIS) by reducing caspase-2-mediated neuronal apoptosis. Given that the molecular structure of the RAIDD DD:PIDD DD complex is avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…1 ). Mild lissencephaly has also been reported in affected individuals [2][3][4][5][6] , and megalencephaly without obvious cortical lamination defects in Cradd null mice 2 . Together with PIDD1 (p53-Induced Death Domain protein 1), CRADD can activate caspase-2-an endopeptidase thought to regulate apoptosis upon DNA damage in the so-called PIDDosome complex [see ref.…”
Section: Introductionmentioning
confidence: 96%
“…1 ). Mild lissencephaly has also been reported in affected individuals [2][3][4][5][6] , and megalencephaly without obvious cortical lamination defects in Cradd null mice 2 . Together with PIDD1 (p53-Induced Death Domain protein 1), CRADD can activate caspase-2-an endopeptidase thought to regulate apoptosis upon DNA damage in the so-called PIDDosome complex [see ref.…”
Section: Introductionmentioning
confidence: 96%
“…How these phenotypes are caused is not fully resolved yet. Although these RAIDD variants were found to still bind to PIDD1 in a cellular system overexpressing the respective proteins, in vitro assays showed that these mutations disrupt interaction [92,94]. Either way, the mutated variants of RAIDD failed to activate caspase-2.…”
Section: Caspase-2 and The Piddosome In Neuronal Development And Disementioning
confidence: 97%
“…If the PIDDosome or an alternative complex containing RAIDD facilitates caspase-2 activation in neurons might depend on the upstream signal, yet both proteins were found to play a role in brain development, and mutations identified in patients were associated with mild forms of lissencephaly and intellectual disabilities [92][93][94][95][96].…”
Section: Caspase-2 and The Piddosome In Neuronal Development And Disementioning
confidence: 99%